2023
DOI: 10.3390/polym15020398
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Grafted Chitosan as Corrosion Inhibitor for Mild Steel Protection

Abstract: Corrosion prevention has been a global phenomenon, particularly in metallic and construction engineering. Most inhibitors are expensive and toxic. Therefore, developing nontoxic and cheap corrosion inhibitors has been a way forward. In this work, L-arginine was successfully grafted on chitosan by the thermal technique using a reflux condenser. This copolymer was characterized by Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). The corrosion inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…19 In comparison to pure CS, CS-IL and CS-IL-SBs have less intense and much broader peaks, indicating that grafting CS with PTSA and Schiff base groups deformed the crystal zone in the CS system, making it less crystalline. 44 Further, the zeta potentials of the synthesized materials are shown in Fig. S4 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…19 In comparison to pure CS, CS-IL and CS-IL-SBs have less intense and much broader peaks, indicating that grafting CS with PTSA and Schiff base groups deformed the crystal zone in the CS system, making it less crystalline. 44 Further, the zeta potentials of the synthesized materials are shown in Fig. S4 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…273 Its multifaceted inhibitive mechanisms contribute to its effectiveness under different corrosive conditions. Also, the corrosion inhibition performance of chitosan has been investigated across a wide range of metal substrates, including carbon steel, [274][275][276][277][278][279][280][281][282][283] aluminum alloys, 284,285 and copper. [286][287][288] Several variables, including pH, temperature, concentration, and exposure period, may affect the effectiveness of chitosan.…”
Section: Green Corrosion Inhibition By Selection: Replacement Of Toxi...mentioning
confidence: 99%
“…273 Its multifaceted inhibitive mechanisms contribute to its effectiveness under different corrosive conditions. Also, the corrosion inhibition performance of chitosan has been investigated across a wide range of metal substrates, including carbon steel, 274–283 aluminum alloys, 284,285 and copper. 286–288…”
Section: Green Corrosion Inhibition: Current Advancements and Future ...mentioning
confidence: 99%
“…The poor solubility of chitosan in water is perhaps considered its only weakness (as an inhibitor), although this problem can be solved by using chitosan derivatives such as carboxymethyl chitosan (while retaining the number of adsorption sites) [92]. Dalhatu et al [95] investigated the effect of L-arginine grafted onto chitosan on the corrosion inhibition of mild steel in 0.5M HCl. The evaluation showed that the inhibition efficiency at optimum concentration rose to 91.4%.…”
Section: Bio-polymersmentioning
confidence: 99%